Using Video to Teach Early Language Concepts and Symbols to Children With Complex Communication Needs. (February 2020) - Huist, Andrea E.; McCarthy, John W.; Boster, Jamie B.; Benigno, Joann P.
Young children who cannot use their natural speech to communicate their daily wants, needs, thoughts, and opinions often rely on augmentative and alternative communication (AAC) strategies that frequently use graphic symbols to assemble messages. Early intervention strategies typically focus on visual scene displays (VSDs) to place target messages in familiar contextualized scenes. However, there are currently no bridging strategies to assist children in moving from VSDs to displays incorporating discrete graphic symbols. The use of contextualized video vignettes is a potential bridge. This preliminary study implemented an intervention using video and play activities paired with a direct instruction approach to teach 10 graphic symbols of important early concepts to children with complex communication needs (CCN). A single-subject multiple baseline across subjects research design was used. Results indicated that the intervention was effective in teaching the target concepts.